Green Recipes for Pyrimidine - Patil, Pradnya; Ansari, Afrin; Tauro, Savita. J.; Nadar, Sahaya (Current Organic Synthesis, 2023)
Pyrimidines serve as key structural components in chemical frameworks and biological processes. Several pyrimidine analogues have been produced over the years by means of traditional methods that necessitated large amounts of solvents, reagents, and, most importantly, additional time, which has led them to become prohibitive. These procedures are now being replaced with more cost-effective adaptive methodologies that incorporate one-pot synthesis and greener approaches involving various green solvents and catalysts. The current review covers a number of green synthetic techniques, including ultrasound-assisted synthesis, visible light irradiation synthesis, solvent-free synthesis, catalyst-free synthesis, microwave-assisted synthesis, and green catalyst synthesis for the synthesis of pyrimidine derivatives. Accordingly, it integrates different strategies to synthesize heterocyclic pyrimidine analogues in a well-organized manner.
Keywords: microwave irradiation